2020
DOI: 10.1080/19476337.2020.1800825
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of flavor changes of grass carp between brine injection and brining at 4°C and 20°C

Abstract: Grass carp is the most important freshwater fish in China, and salting is the main processing method. This study investigated the effect of brine injection on flavor of grass carp muscle compared with brining at low temperature (4°C) and room temperature (20°C) respectively. Salt content, free amino acids, nucleotides, equivalent umami concentration (EUC) and texture were evaluated as flavor indicators during salting. The results showed that brine injection groups reached equilibrium in 3 h and 5 h at 20°C and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Table 1 presents the FAAs detected in the NF, LF, and FLF groups during the fermentation. The results showed that 17 FAAs were identified in the three fermentation groups, including sweet amino acids (tyrosine (Thr), serine (Ser), glycine (Gly), alanine (Ala), and proline (Pro)), umami amino acids (aspartic acid (Asp) and glutamic acid (Glu)), and bitter amino acids (cysteine (Cys), valine (Val), methionine (Met), isoleucine (Ile), leucine (Leu), tyrosine (Tyr), phenylalanine (Phe), histidine (His), and arginine (Arg)) ( Wu et al, 2020 ; Xiang, Xia, Fang, & Zhong, 2024 ; Xiao et al, 2021 ). Extending the fermentation time, the FAA levels in the NF, LF, and FLF groups significantly increased, whereas the Pro content displayed an initial decline, followed by an increase.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 presents the FAAs detected in the NF, LF, and FLF groups during the fermentation. The results showed that 17 FAAs were identified in the three fermentation groups, including sweet amino acids (tyrosine (Thr), serine (Ser), glycine (Gly), alanine (Ala), and proline (Pro)), umami amino acids (aspartic acid (Asp) and glutamic acid (Glu)), and bitter amino acids (cysteine (Cys), valine (Val), methionine (Met), isoleucine (Ile), leucine (Leu), tyrosine (Tyr), phenylalanine (Phe), histidine (His), and arginine (Arg)) ( Wu et al, 2020 ; Xiang, Xia, Fang, & Zhong, 2024 ; Xiao et al, 2021 ). Extending the fermentation time, the FAA levels in the NF, LF, and FLF groups significantly increased, whereas the Pro content displayed an initial decline, followed by an increase.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 3, 17 FAAs were detected in two groups of fermented samples and divided into umami, sweet, and bitter amino acids. Among these amino acids, asparagine (Asp) and glutamate (Glu) are associated with umami taste; tyrosine (Thr), serine (Ser), glycine (Gly), alanine (Ala), and proline (Pro) are closely related to sweet taste; Cysteine (Cys), valine (Val), methionine (Met), isoleucine (Ile), leucine (Leu), tyrosine (Tyr), phenylalanine (Phe), histidine (His), and arginine (Arg) are associated with bitterness (Wu et al, 2020; Xiao et al, 2021). The content of most FAAs including Asp, Thr, Glu, Gly, Ala, Val, Met, Ile, Leu, Tyr, Phe, Lys, and Pro in NF and FF group samples increased dramatically as the fermentation time increased, whereas the content of Ser and Cys were increased then decreased and the content of Arg was decreased then increased.…”
Section: Resultsmentioning
confidence: 99%